Model-based testing essentials : guide to the ISTQB Certified Model-Based Tester foundation level.: guide to the ISTQB Certified Model-Based Tester foundation level. Foundation level (2016) - (Software engineer), Kramer, Anne; Legeard, Bruno
No abstract available